The Regulation Prolems Of Individual Candidates And Single Candidates In The 2020 Elections - Widia Novita Lukitasari WA; Roby Cahyadi Kurniawan; Arizka Warganegara; Hertanto (Kemudi, 2022)
The simultaneous regional elections which will be held in December 2020 are marked by new democratic and political dynamics. The dynamics of the ITU are the birth of a single candidate in several regions that will carry out the regional elections. On the one hand, this shows that the dynamics of democracy on the ground are increasingly showing progress and our society is increasingly "literate" and politically savvy, but on the other hand, it creates new problems whether the regional election will be postponed or issued a Perpu. This happens because legislators do not predict the birth of a single candidate. This fact shows that legislators have not been able to make laws that fulfill philosophical and sociological aspects so that the presence of laws can be well accepted in the midst of society without causing conflict and having a long life. Because it is commonplace in Indonesia that the invitation is only corn.